Phytochemical S-methyl-L-cysteine sulfoxide from Brassicaceae: a key to health or a poison for bees? - Saetbyeol Lee; Pavel Dobes; Jacek Marciniak; Anna Mascellani Bergo; Martin Kamler; Petr Marsik; Radek Pohl; Dalibor Titera; Pavel Hyrsl; Jaroslav Havlik (Open Biology)
Intensive agricultural practices impact the health and nutrition of pollinators like honey bees (Apis mellifera). Rapeseed (Brassica napus L.) is widely cultivated, providing diverse nutrients and phytochemicals, including S-methyl-L-cysteine sulfoxide (SMCSO). While the nutritional impact of rapeseed on bees is known, SMCSO’s effects remain unexplored. We examined SMCSO and its related metabolites—3-methylthiolactic acid sulfoxide and N-acetyl-S-methyl-L-cysteine sulfoxide—analysing their seasonal fluctuations, colony variations and distribution in body parts. Our findings showed that these compounds in bee gut vary among colonies, possibly due to the dietary preferences, and are highly concentrated in bodies during the summer. They are distributed differently within bee bodies, with higher concentrations in the abdomens of foragers compared with nurses. Administration of SMCSO in a laboratory setting showed no immediate toxic effects but significantly boosted bees’ antioxidant capacity. Long-term administration decreased bee body weight, particularly in the thorax and head, and altered amino acid metabolism. SMCSO is found in the nectar and pollen of rapeseed flowers and highly accumulates in rapeseed honey compared with other types of honey. This study reveals the dual impact of SMCSO on bee health, providing a basis for further ecological and physiological research to enhance bee health and colony sustainability.